Simulation and Code Generation for a Parallel Kinematic Manipulator with three Degrees of Freedom - Amann, R.; Geiger, F. (Elektronika ir Elektrotechnika, 2008)
A mechatronic design for a table which is maintained in a horizontal position by actively controlling the length of three prismatic joints is presented. The inclination is measured by means of accelerator sensors based on Micro-Electro-Mechanical Systems technology (MEMS) and the prismatic joints are driven by servo drives. The effectiveness of the design is experimentally validated on a prototype. The paper shows how computer simulation and automated code generation can be used to design and implement mechatronic systems, and demonstrates the benefits of these technologies. Ill. 3, bibl. 9 (in Lithuanian; summaries in English, Russian, Lithuanian).